(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
A large number of researchers have given their best to explain green marketing. Due to globalization and various factors such as a tremendous increase in population growth, global warming has been threatening the future of human beings with the exhaustion of natural resources. This has led to the development of the “green marketing” concept. Green marketing refers to the process of selling products and services based on their environmental benefits. The retail market in India will be more competitive than ever before, and hence Indian retailers have to look for new ways to compete with the best in the world. In retail businesses, environmental issues must be considered. The first step is to promote green products for customers’ daily necessities in general. Many organizations want to turn green, as an increasing number of consumers want to associate themselves with environmentally friendly products. The current research study aims to analyze the attitude of retailers towards green marketing practices in Virudhunagar District. The collected data are analyzed with the help of statistical tools such as percentage analysis, Garrett ranking technique, factor analysis, and cluster analysis. The researcher has given some suggestions based on the findings of the study.